Pengaruh Pembelajaran Fisika Pokok Bahasan Cahaya dengan Model Guided Discovery Learning Terhadap Kemampuan Kognitif Peserta Didik Kelas VIII SMP - Aulia Afifatur Rasyidah; Widayanti Widayanti (Prosiding SNFA (Seminar Nasional Fisika dan Aplikasinya), 2019)
Abstract: This research aims 1). To determine the effect of guided discovery learning models on students’s cognitive abilities 2). Knowing the difference in students’s cognitive abilities between the experimental class and control class. This research is a quasi-experimental research with non-equivalent control group design.The independent variable is guided discovery learning model while the dependent variable is the cognitive ability of students. The sampling technique uses saturated sampling technique because the research subjects are all students of class VIII of SMP Muhammadiyah Purwojati in the 2018/2019 academic year. The instruments used in the form of learning tools, question sheets, and observation sheets. The question sheets is used to obtain data on students’s cognitive abilities and observation sheet is used to obtain data about the activities of students in participating in learning using guided discovery learning model. Data on students’s cognitive abilities were analyzed by descriptive statistics with quantitative methods. the results showed that there was influence of guided discovery learning model. on the cognitive abilities of students as evidenced by the experimental class mean value of 70.32 higher than the control class of 43.27 and there was increase in cognitive ability in the experimental class with an  N-Gain value 0,67 (moderate) higher than the control class with N-Gain of 0.35 (moderate) with an effect size value of 1.80 (very significant).Abstrak: Penelitian ini bertujuan 1). untuk mengetahui pengaruh model pembelajaran guided discovery learning terhadap kemampuan kognitif peserta didik 2). Mengetahui perbedaan peningkatan kemampuan kognitif peserta didik antara kelas eksperimen dan kelas kontrol. Penelitian ini adalah penelitian eksperimen semu dengan nonequivalent control grup design. Variabel bebas berupa model pembelajaran guided discovery learning sedangkan  variabel terikat berupa kemampuan kognitif peserta didik. Teknik pengambilan sampel menggunakan teknik sampling jenuh karena subyek penelitiannya adalah semua peserta didik kelas VIII SMP Muhammadiyah Purwojati tahun pelajaran 2018/2019. Instrumen yang digunakan berupa perangkat pembelajaran, lembar soal uraian dan lembar observasi. Lembar soal digunakan untuk memperoleh data kemampuan kognitif peserta didik  dan lembar observasi digunakan untuk memperoleh data tentang aktivitas peserta didik dalam mengikuti pembelajaran dengan menggunakan model guided discovery learning. Data kemampuan kognitif siswa dianalisis dengan statistik deskriptif metode kuantitatif. Hasil penelitian menunjukkan bahwa  terdapat pengaruh model pembelajaran guided discovery learning terhadap kemampuan kognitif peserta didik  dibuktikan dengan nilai mean kelas eksperimen sebesar 70,32 lebih tinggi dibandingkan kelas kontrol sebesar 43,27 dan terdapat peningkatan kemampuan kognitif pada kelas eksperimen dengan nilai N-Gain sebesar 0,67 (sedang) lebih tinggi dibandingkan kelas kontrol dengan N-Gain sebesar 0,35 (sedang) dengan nilai effect size sebesar 1,80 (sangat signifikan).